Relevansi Teologi Pembebasan Ali Syari’ati dalam Mengatasi Kemiskinan Umat Islam di Indonesia: Sebuah Pendekatan Reflektif - Yuwono, Adhimas Alifian (Media: Jurnal Filsafat dan Teologi, 2025)
The aim of this paper is to elucidate the pertinence of the concepts put forth by Ali Shari'ati, a key figure in the Islamic liberation theology movement, in the context of Muslim impoverishment in Indonesia. The rationale for undertaking this research lies in the prevalence of destitute Muslims in Indonesia, often ascribed to the notion that poverty is predestined by God. This study adopts a qualitative literature review approach, scrutinizing Ali Shari'ati's primary writings in conjunction with pertinent journals, statistical publications, and books addressing the issue of poverty. Through heuristic analysis, these sources are examined to establish their relevance to the aforementioned concern. The outcomes of this investigation reveal several key findings. Firstly, Shari'ati's advocacy for the unity of God, mankind, and nature supports egalitarianism, calling for Muslims to heighten their social awareness through collaboration and mutual assistance. Secondly, individuals are encouraged to embrace Shari'ati's principles of ideology as a means to transcend poverty. Thirdly, Shari'ati's liberation theology underscores Tawhid as a mechanism to eradicate various forms of inequality, including poverty. Thus, this study underscores the intersection between theology and poverty, indicating that endeavors to alleviate destitution should be imbued with a sense of divine purpose.